Sol-gel Synthesis of TiO2 With p-Type Response to Hydrogen Gas at Elevated Temperature - Xie, Lijuan; Li, Zhong; Sun, Linchao; Dong, Baoxia; Fatima, Qawareer; Wang, Zhe; Yao, Zhengjun; Haidry, Azhar Ali (Frontiers in Materials, 2019)
Titanium dioxide is considered as one of the potential candidates for high-temperature gas sensing applications due to its excellent sensitivity and stability. However, its practical use as a gas sensor under elevated conditions is limited on account of its selectivity and insufficient understanding of response conversion from n- to p-type. To this context, the present work is intended to prepare and understand the p-type response of anatase TiO2 toward H2 gas (20-1000 ppm) at elevated temperature (500 C). Sol-gel route is adopted to facilely synthesize powders containing pure and chromium (1-10 at.%) doped TiO2 nanoparticles, which are then brushed onto substrates with already patterned inter-digitated platinum electrodes. In this work, even, the undoped TiO2 samples showed p-type gas sensing response, which then decreased with Cr doping. However, in comparison to previously reported work, the sensing characteristics of all sensors is improved. For instance, 5 at.% Cr-TiO2 showed high response (152.65), fast response and recovery (142/123s) time, and good selectivity to hydrogen against monoxide and methane. Despite better response values, the TiO2 based samples show instability and drift in baseline resistance; such issues were not observed for Cr-doped TiO2 samples (3 at.%). The powders were further analyzed by XRD, SEM, TEM and XPS to understand the basic characteristics, p-type response and stability. Further, a plausible sensing mechanism is discussed on basis of results obtained from aforementioned techniques.